Synthesis of 1, 2‐Dicyano‐3‐arylcycl[3.2.2]azines – First 1, 2‐Dicarbonitriles Based on Cyclazine Heterocycle. Issue 36 (15th September 2020) - Starikov, Andrei S.; Kalashnikov, Valery V.; Tarakanov, Pavel A.; Simakov, Anton O.; Simonov, Sergey V.; Tkachev, Valery V.; Yarkov, Alexander V.; Kazachenko, Vladimir P.; Chernyak, Alexander V.; Zhurkin, Fedor E.; Tomilova, Larisa G.; Pushkarev, Victor E.
Abstract : The first 1, 2‐dicarbonitriles have been prepared for cyclazine systems. In particular, a synthetic procedure to 1, 2‐dicyano‐3‐arylcycl[3.2.2]azines has been developed. Unexpected chlorination of 3‐arylcycl[3.2.2]azine‐1, 2‐dicarboxylic acid derivatives by thionyl chloride at 4‐position was found, which according to theoretical considerations can proceed by the electrophilic (SE Ar) mechanism. The compounds are blue fluorophores in 450–480 nm region with quantum yields in toluene of ca. 30 % for non‐chlorinated derivatives, which decrease to 3–4 % for chlorinated ones. Abstract : The first 1, 2‐dicarbonitriles have been prepared for cycl[3.2.2]azine systems. An unexpected chlorination of cycl[3.2.2]azine core by thionyl chloride at 4‐position in spite of the presence of two electron‐withdrawing groups has been found, and its electrophilic nature was supported by the DFT calculations. The compounds were shown to be promising blue fluorophores for OLED applications.